The Students’ Common Grammatical Mistakes in Writing Argumentative Essay Through Impromptu Theme - Tahang, Heriyanti (Linguistics and ELT Journal, 2024)
The objective of the study was to discover the prevalent grammatical errors made by students in their English writing. This was done by analyzing impromptu essays written by seventh-semester students in the English language education program at the University of Muhammadiyah Sorong. The study utilized a descriptive qualitative research design. The study sample comprised 18 students in their seventh semester, recruited using purposive sampling. The research data were collected from the participants' argumentative essays, which served as the writing assessment centered around the theme, "Grades do not accurately reflect one's intelligence." The researcher employed the qualitative data analysis technique developed by Miles and Huberman. This technique involved data reduction, display, and conclusion drafting through the examination of the students' essay worksheets. According to the analyzed data, it was determined that the students frequently made grammatical errors when composing an argumentative essay. The grammatical errors can be classified into three categories: primary, secondary, and functional. The main category comprised errors in nouns, verbs, determiners, pronouns, prepositions, conjunctions, and adjectives. The secondary group encompassed errors related to numerical representation and verb form. Next, the functional category comprised errors in both the subject and predicate. According to the findings from three kinds of research, the predominant grammatical errors committed by pupils are related to verbs.